FORMULASI SEDIAAN HIDROGEL PENYEMBUH LUKA EKSTRAK ETANOL DAUN BINAHONG (Anredera cordifolia (Ten) Steenis) - , Sri Hartati Yuliani, S.Si., Apt., M.Si.; , Prof. Dr. Achmad Fudholi, DEA, Apt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Binahong (Anredera cordifolia (Ten) Steenis) has been used as wound healing in traditional Indonesian medicine and it is relevant to develop dosage forms of binahong using formulation technology approach. The aims of this research were to study the wound healing activity and irritation potency of ethanolic extract of binahong leaves, the effect of wet and dry heat sterilization to physical properties of the hydrogel base, to study the effect of formula to physical properties and stability of the hydrogel wound healing of etanolic extract of leaves of binahong, and to find out the optimum formula of hydrogel wound healing of etanolic extract of binahong. Pure experimental and factorial design were used in this research. The research was begun with extraction of the binahong leaves and standardized the extract, then looked for the dose of the extract that incorpored to the hydrogel dosage forms. In the other hand, the research about the effect of the heat sterilization to physical properties of hydrogel base was done. The next step was looking for the effect of formula to the physical properties and stability of the wound healing hydrogel of etanolic extract of leaves of binahong and finding out the composition of Carbopol, Na-CMC and Ca-alginate that exhibit good physical properties and stability. The result of this study stated that the highest activity of wound healing was shown by the sample containing 5% of the ethanolic extract of binahong leaves. The percentage activity of wound healing was 63,30%. Irritation appeared on the 10% ethanolic extract of binahong leaves. Wet heat sterilization altered the viscosity and spreadability properties of the hydrogel base was less than dry heat sterilization. Carbopol exhibited the biggest effect on the viscosity, spreadability, extrudability and bioahesive properties of the hydrogel among Na-CMC and Caalginate. It maintained the stability of viscosity and active compound, but exhibited no effect on stability of bioadhesion of the hydrogel. Na-CMC exhibited significant effect on the viscosity, spreadability and extrudability, while no significant effect on the bioadhesion of the hydrogel. It would accelerate the alteration of the viscosity and bioadhesion of the hydrogel, but exhibited no effect on the active compound degree. It exhibited the biggest effect on the alteration of bioadhesion. Ca-alginate exhibited significant effect on all of the physical properties of the hydrogel. It accelerated the alteration of the viscosity, bioadhesion and active compound degree of the hydogel. It exhibited the biggest effect on the alteration of viscosity and active compound degree among Na-CMC and Carbopol. The composition of the Carbopol, Na-CMC and Ca-alginate that exhibit good properties was found in the range of Carbopol 1,03 â 1,07 g, Na- CMC 0,20 â 0,71 g, and Ca-alginate 0,50 â 0,71 g.